(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Single-sex educationrefers most generally to education atthe elementary, secondary, orpostsecondary level in which males or females attend school exclusively with membersof their own sex. This report deals primarilywith single-sex education at the elementary and secondary levels. Research onthe question of whether public single-sex education might be beneficial tomales, females or a subset of either group (particularlydisadvantaged youths) has been limited. However, because there has been aresurgence of single-sex schoolsin the public sector, it was deemed appropriate to conduct a systematicreview of single-sex education research.